Lenvatinib Plus Pembrolizumab for Advanced Endometrial Cancer. Issue 5 (May 2022) - Makker, Vicky; Colombo, Nicoletta; Herráez, Antonio Casado; Santin, Alessandro D.; Colomba, Emeline; Miller, David S.; Fujiwara, Keiichi; Pignata, Sandro; Baron-Hay, Sally; Ray-Coquard, Isabelle; Shapira-Frommer, Ronnie; Ushijima, Kimio; et al.
Abstract : (Abstracted from N Engl J Med 2022;386:437–448) Little consensus exists on optimal treatment for advanced or recurrent endometrial cancer after disease progression with platinum-based chemotherapy. Lenvatinib is a multitargeted tyrosine kinase inhibitor that as a single agent has demonstrated limited efficacy as second-line treatment of recurrent endometrial carcinoma.